(NkR)QÆZX PRIZMU ^ASU (B:s)E (NZB)QÆRKA POEZÆJ (B/s)E - (NsOKOLENKO(B, (No(B. (Ng(B.,s ((NkI)QÇW (B:s)E (NzOLOT)QÆ wOROTA(B,s)E, 2014)
(NdO ZB)QÆRKI (B"(NkRÆZX PRIZMU ^ASU(B" (NUWÆJ[LI KRA]Æ POEZÆÇ(B, (NNAPISANÆ STUDENTAMI kIÇWSXKOGO uNÆWERSITETU æM(B. (NbORISA gRÆN^ENKA(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NuKRA)QÇNSXKA LÆTERATURAs)E -- (NpOEZ)QÆÇs)E